Exploring Community Survival Practices During The Covid-19 Pandemic Through Documentary Filmmaking Insights From Research on The Slopes of Mount Merapi - Rizkya Annissa Farhani; Rocky Prasetyo Jati (International Journal of Science and Applied Science: Conference Series, 2021)
Documentary films are new strategies to deal with the types of data needed by researchers and analysts. Documentary films have also proven to be a methodologically in-depth research approach. This study aims to determine how production management makes "Erupsi dan Pandemi" films during the filmmaking process during the covid-19 pandemic. In this article, we examine and apply the method of creating a documentary on the people of Merapi's slopes and how they cope with the challenges of the 'covid-19 pandemic' and 'alarm eruptions.' The study of related literature supports the creation of selected works to conduct documentaries, observations, documentation, and in-depth interviews. The results showed that finding ideas, determining the purpose of making films, conducting research and observations, making production plans, determining production budgets, and providing equipment and crew management in the pre-production stage. Then at the production stage is briefing, monitoring the filming process while still implementing health protocols. Especially at the last stage, post-production is done by logging, mixing transcripts, scripts, and editing.